Extraforaminal Lumbar Disk Herniations Lead To Neuroplastic Changes: a Study Using Quantitative Sensory Testing. Issue 5 (3rd September 2018) - Tschugg, Anja; Lener, Sara; Hartmann, Sebastian; Fink, Valentin; Neururer, Sabrina; Wildauer, Matthias; Löscher, Wolfgang N.; Thome, Claudius
ABSTRACT: Introduction : Extraforaminal lumbar disk herniations are characterized by distinct clinical features in comparison to paramedian lumbar disk herniations. Methods : We applied the quantitative sensory testing (QST) protocol of the German Research Network on Neuropathic Pain in 63 patients with a single lumbar disk herniation. They were categorized in 2 groups: (I) an intraspinal (group I; n  = 47, 75%) and an extraforaminal (group E; n  = 16, 25%). Results : The wind‐up ratio for assessing endogenous pain‐modulating pathways was higher in group E (2.9 ± 2) than in group I (1.4 ± 1; P  = 0.021). After a subsequent series of pinprick stimuli, an increase in pain assessed by the numeric rating scale could be shown in group E (2.1 ± 2 vs 1.1 ± 1; P  = 0.032). Discussion : Extraforaminal compression is associated with chronic as well as neuropathic pain, presumably caused by direct compression of the dorsal root ganglion, which may preferentially promote specific chronic pain mechanisms. Muscle Nerve 58 : 676–680, 2018